The effect of tax knowledge, taxpayer awareness, and the application of e-filing on individual taxpayer compliance - Lestianingrum, Ekiro; Asmapane, Set (KINERJA, 2023)
This study aims to analyze the effect of tax knowledge, taxpayer awareness and the application of e-filing on individual taxpayer compliance in Balikpapan City. This research is a quantitative research. Data sources are obtained from primary and secondary data by distributing questionnaires and obtaining the number of registered taxpayers. Sampling is carried out by purposive sampling method. The number of samples was determined as many as 100 taxpayers. The data analysis technique used in this study is Statistical Product and Service Solution (SPSS). Based on the results of the analysis conducted, it was concluded that the variables of tax knowledge, taxpayer awareness and the application of e-filing have a significant effect on individual taxpayer compliance variables.